Incidental captures of thresher sharks (Lamniformes: Alopiidae) from turkish coastal waters - Kabasakal, Hakan (Annales. Series historia naturalis, 2007)
Twenty-one alopiid sharks, 2 bigeye thresher (Alopias superciliosus) and 19 common thresher sharks (Alopias vulpinus), were incidentally captured in the coastal waters of Turkey. General information on the captured specimens is reported and the current status of conservation of alopiids is discussed.
Keywords: Alopias superciliosus; Alopias vulpinus; Alopiidae; ribištvo; Turčija; Turkey